Biomechanical evaluation of running and soccer shoes: methodology and testing procedures - Hennig, E. M. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Running shoes are the footwear, that has been explored the most by scientists in the field of biomechanics. Following the running shoe research peak between 1980 and 1990 other products became the focus of interest. In particular, many shoe studies were performed in the field of basketball and other indoor sports. Only recently, soccer boots have received a lot of attention and were explored by various research groups. Other than in running shoes, soccer boots have additional tasks to perform. These shoes are used for kicking, they should provide sufficient traction for rapid cutting manoeuvres and assist the players in rapid acceleration and stopping movements. Especially, the often conflicting demands of injury prevention and high performance properties remain to be solved. Test methods for athletic footwear as well as research results will be presented here. This will demonstrate how important biomechanics has become in providing the necessary knowledge for the design of functional footwear.